445 The long-term natural course of moderate tricuspid regurgitation. (8th December 2021) - Margonato, Davide; Ancona, Francesco; Montalto, Claudio; Manini, Camilla; Melillo, Francesco; Ingallina, Giacomo; Stella, Stefano; Biondi, Federico; Montorfano, Matteo; De Bonis, Michele; Agricola, Eustachio
Abstract: Aims: The epidemiological and clinical burden of tricuspid regurgitation (TR) has lately gained much attention from the scientific community. In fact, recent epidemiological studies report a prevalence of moderate and severe TR in population over the age of 65 screened for valve disease ranging from 2.7% to 4%, with an independent prognostic role clearly worsening long-term survival along with the increasing severity of TR grade. Particularly, as TR is often clinically unsuspected until an advanced stage of congestive heart failure (HF), there is a great need of early diagnosis and long-term appropriate follow-up and management. Nonetheless, data focusing on the clinical and echocardiographic course of a cohort of patients suffering from moderate TR, although eagerly awaited, are lacking. To evaluate and clarify the evolution and the long-term independent clinical outcome of a cohort of patients suffering from moderate functional or organic TR. Methods: We electronically searched for ambulatory and in-patients who underwent transthoracic and/or transesophageal echocardiography with a diagnosis of moderate TR, along with a complete clinical evaluation, in our centre between January 2014 and December 2019. Patients were considered eligible if a second echocardiographic examination including a careful evaluation of the severity of TR and clinical information were available for a minimum follow-up of 6 months. The primary endpoint was all-cause mortality; secondary endpoints were hospitalization for HF and TV intervention, either surgical or percutaneous. Results: We enrolled 130 patients, predominantly female with multiple comorbidities, cardiovascular risk factors and history of atrial fibrillation; TR aetiology was functional in most cases (93 patients, 72%). Over a mean follow-up of 5 years, TR grade progressed to at least severe in 55 patients (42%): at multivariate analyses, diabetes mellitus ( P =0.003), anaemia ( P =0.03) and at least moderate mitral regurgitation or aortic stenosis ( P =0.039) were all predictors of TR severity progression. The primary endpoint occurred in 41(32%) of patients and was significantly more frequent ( P <0.0001) in patients with severe TR at follow-up compared to those without TR severity progression. HF hospitalization and TV intervention occurred in 47 (36%) and 20 (14%) of patients: again, both were significantly more frequent in patients with severe TR ( P =0.0008 and P =0.02, respectively) in comparison to those without worsened TR severity at follow-up. Conclusions: Our results show that moderate TR, over a long-term follow-up period, worsens to at least severe grade in a relevant proportion of patients, conveying a significant independent risk of hard events such as all-cause death, HF hospitalization and TV intervention. Therefore, this cohort of patients should be appropriately managed and closely followed-up in order to avoid adverse clinical events related to the natural course of this valvulopathy.